Myxomycetes : biology, systematics, biogeography and ecology - Alvarado, Carlos Rojas; Stephenson, Steven L. (Academic Press, 2021)
Myxomycetes: Biology, Systematics, Biogeography and Ecology, Second Edition provides a complete collection of general and technical information on myxomycetes microorganisms. Its broad scope takes an integrated approach, considering a number of important aspects surrounding their genetics and molecular phylogeny. The book treats myxomycetes as a distinct group from fungi and includes molecular information that discusses systematics and evolutionary pathways. Written and developed by an international team of specialists, this second edition contains updated information on all aspects of myxomycetes. It incorporates relevant and new material on current barcoding developments, plasmodial network experimentation, and non-STEM disciplinary assimilation of myxomycete information. This book is a unique and authoritative resource for researchers in organismal biology and ecology disciplines, as well as students and academics in biology, ecology, microbiology, and similar subject areas.